Upheaval on the Railways in Germany? - Christian Böttger (Wirtschaftsdienst)
Abstract Deutsche Bahn, the German principal rail and rail infrastructure operator, is in critical condition. Profits are declining, punctuality and reliability are on the lowest level ever. The Federal Minister for Transport announced changes in governance in June that are scrutinized in this article.